The Core of the Esssence of Humans of Pancasila According to Notonagoro: Autonomous and Responsible (Asian Journal of Social Science Studies, 2019)
Humans are different from plants and animals for humans have reason, mind, taste and soul. Many thoughts have arisen regarding humans in philosophy. One of them is Notonagoro’s philosophical thinking that based on Pancasila. Two issues discussed were: what is the essence of humans of Pancasila according to Notonagoro and what is the core of the essence of humans of Pancasila according to Notonagoro. There are three essence of humans of Pancasila according to Notonagoro. They are three monopluralis of humans natures of Pancasila. Each of its consists of two elements. The three natures are: natural structure (susunan kodrat [elements: body and soul]), natural attribute (sifat kodrat [elements: individual beings and social beings]) and natural position (kedudukan kodrat [elements: independent beings and God’s creatures]). These three natures must be kept in balance even though in the context of society, nation and state, three elements such as: soul, social beings and God’s creatures take precedence. These three natures are centered in the soul which produces four godly characters (wisdom, simplicity, determination and justice). The three natures of humans of Pancasila according to Notonagoro can be abstracted into two core: “Autonomous” and “Responsible.” Autonomous of humans of Pancasila includes three elements: body, individual beings and independent beings. Humans have freedom in developing these three elements, but, the freedom itself is not fully independent because humans are bound to the soul with its four godly characters. While responsible includes three other elements: soul, social beings and God’s creatures. Humans have responsibilities both socially (law, ethics, norms, customs) and spiritually (God’s creatures).